Retail Jewellery Omni-Channel Branding and Curating in India - Kesarwani, Shruti (Digital Repository of Theses - SSBM Geneva, 2024)
This dissertation represents the buyer’s choice in purchasing jewellery from either online or offline business model. It will also reflect on the preferred and leading jewellery brands of India. This research presents few findings contributing to the academic and practical fields in Indian jewellery market work is towards the theoretical foundation with inspirational study on the jewellery market in India, contributing to its growth adding value based on patterns of jewellery buyer’s. The research is based on the case study of a renowned jewellery brand pan India. This study is based presented with the discussions and underlying reasons with an interesting insight followed by the interviews of the volunteers, the qualitative research method with the questions asked gaining in-depth understanding on the adopted measures followed by the jewellery buyers in India over brands Jung Choo, H., Moon, H., Kim, H. and Yoon, N. (2012). This study contributes to theory of jewellery brand creation and configure buying patterns of jewellery buyers in India by doing a case study on a jewellery brand exploring on its strategizes that impact the buyer’s purchase both online and offline. This research will hence help into acknowledging the preferred analytics encoded in jewellery branding to provide value base services required by the choicest masses. According to (Knapp, 1999) Study have been done over this pattern by various patrons and I tend to present an exciting input for the growth of jewellery industry with a branded outlook for both online and offline mediums, studying the existing data with the new submission on the area of buyer’s interest as time flickers with variable interest on how branding affects the mindset and how to maintain that interest equilibrium amongst the buyer’s by adapting to something new in intervals. The importance of creating a brand is that the more your buyer’s know about you, the more likely they are to get back on the purchases. (Kunz, May and Schmidt, 2020) Branding distinguishes your state-of-art jewellery from the others present in the market, giving it a niche in the society. The brand should reflect ‘Why it should be chosen over others? The findings of this brand creating study signifies that usually brands don’t have a one-size-fits-all definition. (Dewey, 2024) The first impression is the ‘LOGO’ that objectifies you as a whole. Also, there is so much more that adds-on to successfully creating a jewellery brand image. The results, recommendations and discussions may be referenced for those incorporations of branding by Indian industry who are actively associated in the market with dull or no presence online or offline. (Moore and Birtwistle, 2005) However, for the newly acquired jewellery brands, branding can lead to a lustrous advertising, creating distinctive edge in the market representation and its growth. The distinctive feature with radiant traits that is not served by the rest but only a particular brand becomes an asset as a value addition to customers is the base of this study.